Grafeno: el alótropo más prometedor del carbono - Méndez Medrano, Ma. Guadalupe; Rosu, H. C.; Torres González, L. A. (Acta Universitaria, 2012)
After a brief review of the discoveries of the allotropes of carbon known up to the present time,we focus on graphene, which is the most recent one. The remarkable material properties ofgraphene are due to its relativistic electrons and give a lot of hopes for many technologicalapplications of high impact.
Keywords: Array; Array; Array; Array